Penguatan Pelindungan Data Pribadi Melalui Otoritas Pengawas Di Indonesia Berdasarkan Perbandingan Hukum Hong Kong Dan Singapura - Azza Fitrahul Faizah; Sinta Dewi Rosadi; Garry Gumelar Pratama; Ananda Fersa Dharmawan (Hakim, 2023)
Law Number 27 of 2022 concerning Personal Data Protection (UU PDP) has directly mandated the establishment of a data protection authority which determined by the President. The LPPDP has projected to become an authority that acts as a supervisor and law enforcer for personal data protection in Indonesia, the LPPDP must be able to perform its functions, duties, and authorities independently. The several DPA forms can be considered to establish LPPDP in Indonesia. This journal article examines the necessity of establishing DPAs as an essential component in strengthening personal data protection laws in Indonesia through a comparison of law and practices in Hong Kong and Singapore. The research utilizes a comparative normative approach with descriptive-analytical specifications, comparing the mechanism of the supervisory authority and positive laws related to privacy and personal data protection in Hong Kong and Singapore. This study has resulted in several results: First, the existence of an independent LPPDP will strengthen the personal data protection law effectively and comply the adequate level of protection with other developed countries. Thus, the President must immediately establish LPPDP regarding the minimum requirements for the DPA's establishment in international practice. Second, there are several recommendations that can be applied in establishing the formation of LPPDP, whether in the form single supervisory authority or ministry based-models.